The Compound Risk Framework: Assessing fragility and key drivers of food insecurity in Haiti, Mozambique and Ghana - Minoarivelo, Onivola Henintsoa; Craparo, Alessandro; Basel, Ashleigh Megan; Nguyen, Kien Tri; Ouedraogo, Yacouba; Douglas, Wesley; Melly, Brigitte; Dao, Hoa; Carneiro, Bia; Pacillo, Grazia; Laderach, Peter (2025)
Climate variability is increasingly impacting natural and human systems, exposing societies to compound and interrelated environmental, socioeconomic, and political crises. The landscape of global conflict has intensified, with more countries experiencing violent conflict than at any point in the last three decades. However, our approaches to these issues are often siloed and fragmented, rendering them inadequate at capturing the complexity of interconnected systems. One of the many compound impacts is the escalating threat to food security. The role of climate variability has increased in recent decades, owing to more frequent extreme events, exacerbating existing vulnerabilities of crops, ecosystems, people and communities. In order to understand and address the fragility of these complex systems, we require innovative and integrated approaches to establish effective early warning measures.